Multifunctional nanowires and hierarchical 3D nanostructures of material composites for energy storage - Vidyadharan, B.; Pal, B.; Izan Izwan, Misnon; Elim, Hendry Izaac; Rajan, Jose (IOP Publishing, 2020)
Composites of functional materials have long been synthesized for achieving enhanced physical and chemical properties. In this era of energy intensive electronics and electric vehicles, energy storage devices utilising composite materials could offer improved performance at a lower cost. Furthermore, if the composite materials are synthesized in one-dimensional morphology at a nano level, conductivity and thus electrical properties could be multiplied. A range of materials with different functionalities have been synthesized by our group recently; as a typical example synthesis of a composite nanowire containing NiO and CuO for supercapacitive energy storage is detailed in this paper and compared the performance of the composite wires with its component binary wires. The materials were synthesized by electrospinning technique and characterized for their structure, microstructure, surface properties and electrochemical properties. The results shows that a composite wire containing materials for similar electrical conductivity would lead to improved charge storage performance than their single component counterparts.